Assessing the potential and determinants of food crop sub-sector production in East Java, Indonesia - Fahmi Tanjung (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to identify the base and non-base areas within the food crop sub-sector and examine the relationship between agricultural land area, labor (farmers), and the Human Development Index in the production zones of the food crop sub-sector.Method — The research utilized Location Quotient analysis and logit regression analysis, employing the SPSS application as the analytical tool. The study sample consisted of 38 regencies/cities from East Java Province.Result — The results of this research reveal the specific areas encompassed within the food crops sub-sector base in East Java Province, namely: Pamekasan Regency, Blitar Regency, Madiun Regency, Nganjuk Regency, Probolinggo Regency, Trenggalek Regency, Jombang Regency, Kediri Regency, Magetan Regency, Ngawi Regency, Tuban Regency, Ponorogo Regency, Bangkalan Regency, Bondowoso Regency, Lamongan Regency, Sampang Regency, Situbondo Regency, Tulungagung Regency, and Pacitan Regency. Furthermore, the research outcomes highlight a significant correlation between the agricultural labor force (farmers) and production levels, encompassing both the base and non-base sectors of the food crop sub-sector within East Java Province. Conversely, the study reveals that the Human Development Index (HDI) and land area do not exert a statistically significant influence on production.Contribution — This study contributes by determining the regencies/cities in East Java Province classified as base and non-base areas of the food crops sub-sector. It explores the factors leading to such classifications. Unlike previous research focusing solely on base and non-base areas, this study comprehensively analyzes both categories within the food crops sub-sector.